Unusual gastric foreign body obstruction in three dogs - Thilagar, Sundararajan; Chen, Hui Cheng; Khor, Kuan Hua; Rahman, Nor Alimah; W. P., Vinita (Veterinary Association Malaysia, 2007)
Three cases of unusual gastric foreign body obstruction in three dogs are discussed in this paper. The foreign bodies - durian fruit seed (Durio species), a pair of stockings and cleaning sponge - were diagnosed using survey radiography and barium contrast radiography. The dogs presented with signs of dullness, anorexia, weight loss and chronic intermittent vomiting. Foreign bodies were removed surgically following gastrotomy.